Self-reliant in defense industries: Case study Indonesia - Mohamad Irfan; Sulaeman Rahman Nidar; Yudi Azis; Sunu Widianto (Cogent Business & Management, 2023)
Many developing countries are supporting their local defense industries to increase self-sufficiency, although they remain dependent on imports from foreign suppliers. Little is known about factors that may explain the self-reliance aspect of these industries. Therefore, this study aims to examine factors related to business performance that can explain the independence of the defense industry in developing countries. In this experiment, the implemented system covers four aspects of organizational performance, namely dynamic capabilities, high-performance work systems, technological innovation, and business model innovation. The system then investigates the mediation of business model innovation between the first three factors and organizational performance. Based on this analysis, Partial Least Squares-Structural Equation Modeling is used on data from 70 Indonesian defense industries. The results show that high-performance work systems and technological innovation significantly explain the variation of model innovation. By using business model innovation interventions, these two factors also explain business performance. These conditions imply the importance of prioritizing the following: human resource practices that promote employee self-improvement, motivation, and engagement, and adopting new or improved technologies into products and processes. The model built is novelty in the development of the defense industry, especially in developing countries.
Keywords: 650; business model innovation; case of Indonesian defense industries; defense business performance; dynamic capabilities; high-performance work systems; PLS-SEM; technological innovation